(3QSGdI aj GdHSedIs - (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe, (B337 (3g` s
(3ChdgG (B:s
(3Efi JOHQJ bhd Gddg Ld GSeg HSe Gddg GdQMef GdQMje ahLOJ ajg KeGfjf SDGdkG efgG ai bhdg HSe GQHYhf SDGdkG hYgf GSe Gdgd Ld KfGDg hJbOSJ GSeGDg YTQhf s
(3BNQgG (B:s
(3hajgG PcQfG ef GdGUhd hgh MSHfG hfYe Gdhcjd s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3fMh (B67) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs